Impact of metabolic and cardiovascular disease on COVID-19 mortality: A systematic review and meta-analysis. Issue 6 (November 2021) - Sahni, Shubham; Gupta, Gaurav; Sarda, Radhika; Pandey, Shivam; Pandey, R.M.; Sinha, Sanjeev
Abstract: Background and aims: This meta-analysis aims to highlight the impact of cardio-metabolic comorbidities on COVID-19 severity and mortality. Methods: A thorough search on major online databases was done for studies describing the clinical outcomes of COVID-19 patients. We used random-effects model to compute pooled estimates for critical or fatal disease. Results: A total of 20, 475 patients from 33 eligible studies were included. Maximum risk of development of critical or fatal COVID-19 disease was seen in patients with underlying cardiovascular disease [OR: 3.44, 95% CI: 2.65–4.48] followed by chronic lung disease, hypertension and diabetes mellitus. Of the total cases, 64% had one of the four comorbidities with the most prevalent being hypertension with a pooled prevalence of 27%. Conclusions: Presence of comorbidities like cardiovascular disease, chronic lung disease, hypertension and diabetes mellitus led to a higher risk of development of critical or fatal COVID-19 disease, with maximum risk seen with underlying cardiovascular disease. Highlights: Diabetes mellitus, hypertension and cardiovascular disease increased the risk of critical or fatal COVID-19. Most prevalent comorbidity amongst COVID-19 patients was hypertension. Strongest risk factor for a poor outcome was underlying cardiovascular disease.